DEFINITION OF DYNAMIC FEEDBACK BY THE METHOD OF MODAL CONTROL - Tunik, A. A.; Abramovich , E. A. (Problems of Informatization and Management, 2021)
In this talk, we propose a method for placing dynamic feedback poles using modal control in a stable region. In the previously known literature, this problem was solved for a continuous system. New in the work is the solution of this problem for a discrete control system. An example of modal control for discrete control systems for the longitudinal motion of a small UAV is given.